Effect of Sugar Factory Distillery Spent Wash (DSW) on the Growth Pattern of Sugarcane (Saccharum officinarum) Crop - M.K. Mishra2, P. Rath1*, G. Pradhan1 (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Distillery spent wash is a rich source of organic matter and nutrients like nitrogen, phosphorus, potassium, calcium and sulfur. In addition, it contains sufficient amount of micro-nutrients such as iron, zinc, copper, manganese, boron, and molybdenum. A field experiment was conducted with different dilutions of distillery spent wash using sugar cane (Saccharum officinarum) variety Co1274 as test crop. The experiment was formulated with four treatments (25%, 50%, 75% and 100%) with three replicates, with a set of control for comparison. The growth parameters like height of the plant, length of the leaves, breadth of the leaves, girth of the stem, leaf area index, number of leaves per plant, no. of tillers per plant etc of the plant enhanced with increase in concentration of distillery spent wash up-to 75%. But in 100% concentration of distillery spent wash all the growth parameters showing a declining trend from the control. This increase in the parameters is statistically significant.